Pathogenetic aspects in precursor lesions of gastrointestinal tumors - Rau, Tilman (Pathologe, 2016)
The pathogenesis of precursor lesions of gastrointestinal tumors is manifested in many ways. In the esophagus an aberrant genetic expression of intestinal transcription factors, such as CDX2 is initiated by local environment factors. During the subsequent dysplasia to carcinoma sequence, chromosomal gain and loss of genes occurs. A 4-color fluorescence in situ hybridization (FISH) assay can be applied in dysplasia as well as in Barrett's adenocarcinoma to define prognostic marker combinations. In the gastric carcinogenesis sequence the gene expression of CDX1 is regulatively dependent on an interplay between inflammation and promotor methylation. In the colon sessile serrated adenomas show a sequence with initial BRAF mutation and late onset of MLH1 promotor hypermethylation with consecutive potential cancer progression. This event is accompanied by an increase of intraepithelial lymphocytes, which is an easy to use tool for routine diagnostics using H&E sections. Next generation sequencing (NGS) investigations of germline mutations in colorectal cancer revealed a spectrum of mutations with low penetration in the field of mismatch repair proteins as well as the APC gene. An individual risk stratification for penetration of these germline mutations is necessary. In conclusion, genetics, phenotypes and terminology of gastrointestinal precursor lesions are unified to a mutually influencing concept within medicine.
EVALuna2:6910